2020
DOI: 10.3389/fnhum.2020.00298
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Substance Use and the Brain: Behavioral, Cognitive and Neuroimaging Correlates

Abstract: Adolescence is an important ontogenetic period that is characterized by behaviors such as enhanced novelty-seeking, impulsivity, and reward preference, which can give rise to an increased risk for substance use. While substance use rates in adolescence are generally on a decline, the current rates combined with emerging trends, such as increases in e-cigarette use, remain a significant public health concern. In this review, we focus on the neurobiological divergences associated with adolescent substance use, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 325 publications
(485 reference statements)
1
34
0
1
Order By: Relevance
“…Cannabis use status was not associated with imaging outcomes in males, but males with higher monthly cannabis use and earlier cannabis use onset had lower cerebellar gray and white matter volume, respectively (Rossetti et al, 2019). Other studies have identified sex differences in neural circuitries underlying SUDs using resting state functional connectivity, and these have been reviewed elsewhere (Hamidullah, Thorpe, Frie, Mccurdy, & Khokhar, 2020;Rakesh, Allen, & Whittle, 2020).…”
Section: Finally Preliminary Work From the Enigma-addiction Workingmentioning
confidence: 99%
“…Cannabis use status was not associated with imaging outcomes in males, but males with higher monthly cannabis use and earlier cannabis use onset had lower cerebellar gray and white matter volume, respectively (Rossetti et al, 2019). Other studies have identified sex differences in neural circuitries underlying SUDs using resting state functional connectivity, and these have been reviewed elsewhere (Hamidullah, Thorpe, Frie, Mccurdy, & Khokhar, 2020;Rakesh, Allen, & Whittle, 2020).…”
Section: Finally Preliminary Work From the Enigma-addiction Workingmentioning
confidence: 99%
“…The adolescent brain undergoes critical neuronal and structural development, making adolescence a period of vulnerability to the effects of drugs 9 , with brain imaging studies suggesting altered brain structure and function in adolescent users compared to non-users 9 . However, the causal consequences of adolescent co-use cannot be systematically examined in humans and thus, animal models are required to explore the cause-effect relationship.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, adolescents are especially vulnerable to drug use. Cannabis is one of the most commonly used drugs among this age group, so understanding the impact of adolescent cannabinoid exposure is of utmost importance (Hamidullah et al, 2020(Hamidullah et al, , 2021. Previous human and animal studies suggest that adolescent exposure to cannabinoids dysregulates ECS activity, which may have long-term behavioral implications that can persist into adulthood (Hamidullah et al, 2020;Thorpe et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis is one of the most commonly used drugs among this age group, so understanding the impact of adolescent cannabinoid exposure is of utmost importance ( Hamidullah et al, 2020 , 2021 ). Previous human and animal studies suggest that adolescent exposure to cannabinoids dysregulates ECS activity, which may have long-term behavioral implications that can persist into adulthood ( Hamidullah et al, 2020 ; Thorpe et al, 2020 ). For instance, treatment of adolescent rats with the CB1R/CB2R agonist WIN55,212-2 ( Schoch et al, 2018 ) or the CB1R/CB2R partial agonist and the primary psychoactive constituent of cannabis Δ9-tetrahydrocannabidiol (THC) ( Kruse et al, 2019 ) have been shown to modulate the response to food-predictive cues in adulthood.…”
Section: Introductionmentioning
confidence: 99%